Ancient Text Messages of the Yoruba Batá Drum Cracking the Code. Amanda Villepastour. 2010. Farnham: Ashgate, SOAS Musicology Series. 173 pp. photos, transcriptions, CD. ISBN 978-0-7546-6753-7 hb, ISBN 0754667537 pb. - Kubik, Gerhard (International Library of African Music, 2010)
pages: 124-125
Keywords: African Music; Batá Drum; Yoruba Art